Optimizing Navigation Channels through Hydrodynamic and Sedimentation Modeling: A Case Study of the Barito River Estuary, South Kalimantan - Aulia De Silva Nusantara Candida; Khomsin; Aldila Syariz Muhammad; Cahyo Utomo Andik; Rafly Rahardian Muhammad (BIO Web of Conferences)
The Barito River Estuary in South Kalimantan plays a crucial role in Indonesia’s maritime transportation, particularly in trade and coal transshipment. As the largest river in Kalimantan, with its estuary facing the Java Sea, it supports regional economic activities. However, channel siltation due to sedimentation presents significant challenges, exacerbated by natural changes along the river and estuary. Sediment grain size and current velocity are key factors in sediment movement. This study uses Delft3D software to model hydrodynamic and sedimentation patterns in the estuary. The model reveals significant variations in current speed and direction between tidal cycles and seasons. During the wet season, stronger currents, averaging 0.1 m/s, flow from upstream to downstream, distributing sediment more evenly across the estuary. In contrast, the dry season shows increased sedimentation, concentrating in specific areas. The sedimentation model estimates that during the dry season, sediment deposition could reach 0.100 meters over six months (0.017 meters per month), while in the wet season, it is approximately 0.060 meters over six months (0.010 meters per month). These dynamics impact navigation channels, particularly during the dry season when sedimentation narrows and shallows the channels, limiting access for larger vessels and increasing the risk of grounding. This study aligns with SDG 9: Industry, Innovation, and Infrastructure, as ensuring efficient navigation channels is vital for fostering sustainable industrial growth and improving maritime logistics.